The Decomposition of Effects in Path Analysis - Alwin, Duane F.; Hauser, Robert M. (American Sociological Review, 1975)
of a JSTOR transmission may be copied, downloaded, stored, further transmitted, transferred, distributed, altered, or otherwise used, in any form or by any means, except: (1) one stored electronic and one paper copy of any article solely for your personal, non-commercial use, or (2) with prior written permission of JSTOR and the publisher of the article or other text. Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission. American Sociological Review is published by American Sociological Association. Please contact the publisher for further permissions regarding the use of this work. Publisher contact information may be obtained at